CHARACTERS OF PERSONAL TEMPERAMENT IN SPEECH EXPRESSION - S.Qurbonova (Scholar Express Journal, 2023)
The article talks about the influence of personality traits, in particular, temperament, on text structure. It describes linguocholeric, linguosanguinic, linguophlegmatic, and linguomelancholic types
Keywords: speech; personality traits; temperament; linguocholeric